2001
DOI: 10.1046/j.1439-0329.2001.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long‐term exposure to simulated acid rain on the development of pine wilt disease caused by Bursaphelenchus xylophilus

Abstract: To elucidate the synergetic effects of acid rain on the development of pine wilt disease, we measured the sap¯ow rate in the stems and the chlorophyll content in the needles of 10-year-old Japanese black pine trees, Pinus thunbergii and 12-year-old Japanese red pine trees, Pinus densi¯ora, after exposure to simulated acid rain (SAR, pH 3) or tap water (TW, pH 6.3) as a control. The heat pulse method was used for the estimation of the sap¯ow rate. No apparent difference was found in the sap¯ow rate between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…They further concluded that there was little evidence of direct effects of CO 2 or UVB and that precipitation effects had not been studied sufficiently to draw a general conclusion. Other factors such as acid rain may also influence disease (6,7,12).…”
Section: Pathogen and Vector Responses To Climate Changementioning
confidence: 99%
“…They further concluded that there was little evidence of direct effects of CO 2 or UVB and that precipitation effects had not been studied sufficiently to draw a general conclusion. Other factors such as acid rain may also influence disease (6,7,12).…”
Section: Pathogen and Vector Responses To Climate Changementioning
confidence: 99%
“…The avirulent isolates have a lower potential to invade the bark tissues of pine shoots (Asai, 2002), and lower ability to disperse (Ichihara et al, 2000) and propagate (Kiyohara and Bolla, 1990) within healthy pine trees. The number of nematodes of avirulent isolates carried by the vector beetle, Monochamus alternatus Hope, is far fewer than that of the virulent isolates (Aikawa et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Acid rain affects pine's normal growth directly, altering the contents of free amino acids in needles (Huhn and Schulz 1996), decreasing photosynthesis rate (Reich and Schoette 1987;Shan and Feng 1988) and inflecting leaf nutrient balance (Thelin et al 1998). It can also affect it indirectly through aluminium toxicity (Tepper 1989;Nowak and Friend 1995) and changes in the rates of insect herbivory (Asai and Futai 2001). In southern China, sun rays are always fierce and acid rain becomes a serious environmental problem, however, we still have little knowledge concerning the way they interact and the ability of light protection mechanisms of pines to sustain high irradiance when exposed to acid rain.…”
Section: Introductionmentioning
confidence: 99%